2021
DOI: 10.2334/josnusd.20-0443
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for abutment and implant fracture after loading

Abstract: Purpose: Implant component fractures are one of the most serious complications in implant treatment. With a better understanding of the risk factors for fracture in the preoperative, surgery, superstructure, and post-loading phases of implant treatment, low-risk treatment could reduce implant component fractures, leading to a better prognosis. The aim of this study was to clarify the risk factors for abutment and implant fractures that occur after loading, and to perform a retrospective, approximately 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…At the end of the study, there were 14 abutment fractures (0.14%) and four implant fractures (0.04%) in 10,231 LA implants. During the same period, there were 14 abutment fractures (0.61%) and five implant fractures (0.22%) in 2307 SA implants, corresponding to a lower fracture percentage than those observed in previous studies involving Asian cohorts (Murakami et al, 2020; Shim & Yang, 2015). Shim et al reported ten abutment fractures in 450 SA implants (2.2%), and Murakami et al revealed 18 abutment fractures (1.6%) and eight implant fractures (0.7%) in 1126 SA implants over a 10‐year follow‐up period.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…At the end of the study, there were 14 abutment fractures (0.14%) and four implant fractures (0.04%) in 10,231 LA implants. During the same period, there were 14 abutment fractures (0.61%) and five implant fractures (0.22%) in 2307 SA implants, corresponding to a lower fracture percentage than those observed in previous studies involving Asian cohorts (Murakami et al, 2020; Shim & Yang, 2015). Shim et al reported ten abutment fractures in 450 SA implants (2.2%), and Murakami et al revealed 18 abutment fractures (1.6%) and eight implant fractures (0.7%) in 1126 SA implants over a 10‐year follow‐up period.…”
Section: Discussionmentioning
confidence: 53%
“…Asian cohorts (Murakami et al, 2020;Shim & Yang, 2015). Shim et al reported ten abutment fractures in 450 SA implants (2.2%), and Murakami et al revealed 18 abutment fractures (1.6%) and eight implant fractures (0.7%) in 1126 SA implants over a 10-year followup period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and articles that did not fulfill the inclusion criteria, 46 potentially pertinent records remained (κ = 0.88). After the full texts were evaluated, 34 studies were further excluded, for the following reasons: Two 26,27 studies included implantsupported complete-arch prosthesis patients; 12 studies did not report implant length; 6,[28][29][30][31][32][33][34][35][36][37][38] 11 studies combined data for short and long implants, [39][40][41][42][43][44][45][46][47][48][49] and 9 studies did not involve short implants. [50][51][52][53][54][55][56][57][58] Ultimately, 12 studies satisfied the inclusion cri-teria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…28 As a result, the crown will not fall off even if the abutment screw is loosened, and thus the abutment often remains stably fixed even with a loosened screw. 6 This may be one of the reasons why ASL is rare after the use of this system. In addition, there was no significant difference in ASL between the indexed and non-indexed abutments.…”
Section: Discussionmentioning
confidence: 99%